The effect of overskilling dynamics on wages - Kostas G. Mavromaras; Stéphane Mahuteau; Peter J. Sloane; Zhang Wei (Institute for the Study of Labor (IZA), 2012)
We use a random effects dynamic probit model to estimate the effect of overskilling dynamics on wages. We find that overskilling mismatch is common and more likely among those who have been overskilled in the past. It is also highly persistent, in a manner that is inversely related to educational level. Yet, the wages of university graduates are reduced more by past overskilling, than for any other education level. A possible reason for this wage effect is that graduates tend to be in better-paid jobs and therefore there is more at stake for them if they get it wrong.
Keywords: J24; J31; 330; mismatch; overskilling; wages; panel dynamic estimation; Unterbeschäftigung; Akademiker; Bildungsertrag; Lohnstruktur; Qualifikation; Australien